“Making the Old Fashion Shines Again”: A Review on Instructional Media and Innovation Course at STKIP PGRI Banjarmasin - Yasyir Fahmi Mubaraq; Imam Hendra Saputra (UMBanjarmasin, 2020)
Instructional media and innovation course is a compulsory subject for the pre-service teachers who are studying at STKIP PGRI Banjarmasin - a teacher training and education collage. This course requires the students to master the recent media design and educational technology. The old fashion media such as puppets, big books, and miniature are also taught to the course participants. Which at the same time, they also learn to use the recent media such as Edmodo, Kahoot!, and the newest related educational technology. This paper illustrates how the lecturers design their teaching and learning plan as well as underlines some recommendations for this course.